CONTROLLING INVENTORY LEVELS OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA: EFFECT ON FIRM PROFIT (Journal of Global Accounting, 2023)
The nub of this study is to examine the effect of inventory control on the profitability of listed industrial goods firms in Nigeria. The specific objectives of the study were to examine the extent to which inventory conversion period, inventory to sales ratio and inventory turnover ratio affect return on assets. Ex-post facto design was deployed for the study. A sample size of seven (7) listed industrial goods firms was purposively selected from the population of thirteen (13) listed industrial goods manufacturing firms in Nigeria. Cross-section Fixed Effect Model was utilised in estimating the test results at 5% level of significance. The findings include: inventory conversion period does not have a significant effect on return on assets (β1 = 0.000108, t-Statistic = 1.140571, Prob>|t| = 0.2586); inventory to sales ratio significantly and negatively affects return on assets (β2 = -2.955392, t-Statistic = -5.534244, Prob>|t| = 0.0000); inventory turnover ratio significantly and negatively affects return on assets (β3 = -0.057291, t-Statistic = -8.533998, Prob>|t| = 0.0000) of listed industrial goods manufacturing firms in Nigeria. In conclusion, the earnings after tax of the firm is improved through the instrumentality of effective inventory control techniques. It was recommended that potential investors in listed industrial goods firms should watch out for firms with a lower inventory as a percentage of sales since lower inventory to sales ratio is an indication that the firm is making more sale per item in the firm’s inventory.
Keywords: Firm Profitability; Inventory Control; Inventory Conversion Period; Inventory to Sales Ratio; Inventory Turnover Ratio; Return on Assets